APLIKASI PENGHITUNG PERSOALAN TEORI HIMPUNAN BERBASIS ANDROID DENGAN BAHASA PEMPROGRAMAN KOTLIN - hendro purwoko; Bayu Jaya Tama (Jurnal THEOREMS (The Original Research of Mathematics), 2022)
Mathematics can be combined with Technology in the field of Information Systems because of its similarities to thinking with logic. This combination is applied in discussing Set Theory by creating Android-based applications using the Kotlin programming language.  The application development stage uses the Waterfall type SDLC (Software Development Life Cycle) so that each stage is carried out properly and performs testing by making several simulations so that each calculation produces the correct value.  The output of the research results in an Android-based Set Theory calculator application with accurate calculations.